INNOVATION TO PREVENT KEK (Chronic Energy Deficiency) IN PREGNANT WOMEN WITH ROTTAYAM - Indrayani, Triana; Azizah, Uswatun Awa; Fanny, Aesza Okty Zull; Berliana, Fara; Septiarani, Disty; Munjanah, Yuliani; Megawati, Siska; Hardianti, Siti (Yayasan Education and Social Center, 2024)
Based on the results of a preliminary survey in Tanjung Anom Village, Mauk District, Tangerang Regency, the prevalence of KEK (Chronic Energy Deficiency) in pregnant women in October was 10.6%, where the RPJMN target in 2024 was 10%. Of the 66 pregnant women, 7 pregnant women experienced KEK. SEZ is a condition in which a person suffers from an imbalance in nutritional intake (energy and protein) that lasts for a long time. Pregnant women who experience KEK will have problems in pregnancy, childbirth, and postpartum. In addition, it will also have an impact on fetal development. The government has made efforts to help reduce the incidence of SEZs in pregnant women by providing regular supplementary food to pregnant women. However, these efforts still need to achieve the expected target. The purpose of community service is to increase the knowledge of pregnant women, cadres, and community leaders about the impact of pregnant women experiencing KEK and how to handle it. Participants in this activity were 15 pregnant women who experienced SEZs, Posyandu Cadres, and community leaders. This activity began by conducting a preliminary survey and a forum discussion group (FGD) to determine the priority of problems and interventions to be given. The intervention implementation was carried out through pretest and post-test assessments to see the effectiveness of the counseling provided. The evaluation results found an increase in knowledge in pregnant women with an average score of 62 from the pretest results and 98 postes results. So, it can be concluded that pregnant women understand the impact of SEZs during pregnancy. We advise pregnant women to be able to meet a balanced nutritional intake during pregnancy by consuming foods that are high in calories and protein, by the innovation given, namely GUDEK ROTTAYAM, which means Movement of bUmil with Cakes, Rolade Tofu, Eggs, Chicken and baYAM